Socioeconomic distribution of emissions and resource use in Ireland - Seán Lyons; Anne Pentecost; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2012)
This paper uses the ESRI's ISus model to explore the distributional differences in emissions by household type. Most greenhouse gas and metal emissions are emitted via indirect means, although direct sources of emissions play a role for CO2, SO2 and CO. The results suggest that the richest decile is the biggest emitter and poorer and larger households are seen to emit the least per person.
Keywords: 330; pollution; household emissions; distributional analysis